Incidence and risk factors for readmission to a paediatric intensive care unit. Issue 3 (1st October 2019) - Konishi, Umi; Hatachi, Takeshi; Ikebe, Ryo; Inata, Yu; Takemori, Kazumi; Takeuchi, Muneyuki
Abstract: Background: Unscheduled readmission to a paediatric intensive care unit can lead to unfavourable patient outcomes. Therefore, determining the incidence and risk factors is important. Previous studies on such readmissions have only focused on the first 48 hours after discharge and described the relative risk factors as unmodifiable. Aim: To identify the incidence and risk factors of unscheduled readmission to a paediatric intensive care unit within 7 days of discharge. Design: This was a retrospective observational study. Methods: Our study population comprised consecutive patients admitted to the paediatric intensive care unit of our tertiary hospital in Japan in 2012 to 2016. We determined the incidence of unscheduled readmission to the unit within 7 days of discharge and identified potential risk factors using multivariable logistic regression analysis. Results: Among the 2432 admissions (1472 patients), 60 admissions (2.5%, 44 patients) were followed by ≥1 unscheduled readmission. The median time to readmission was 3.5 days. The most common causes for readmission were respiratory issues and cardiovascular symptoms. The significant risk factors for readmission within 7 days of discharge were unscheduled initial admission (odds ratio [OR]: 3.02; 95% confidence interval [CI:] 1.45‐6.31), admission from a general ward (OR: 5.13; 95% CI: 1.75‐15.0), and withdrawal syndrome during the initial stay (OR: 3.95; 95% CI: 1.53‐10.2). Conclusions: The incidence of unscheduled readmission within 7 days was not high (2.5%), and one of the three identified risk factors for readmissions (withdrawal syndrome) is potentially modifiable. Relevance to clinical practice: Appropriate treatment of withdrawal syndrome may reduce readmissions and improve patient outcomes. Although unscheduled initial admission and admission from general ward are not modifiable risk factors, careful discharge judgement and follow up after discharge from paediatric intensive care units for high‐risk patients may be beneficial.